2012
DOI: 10.1148/rg.327125032
|View full text |Cite
|
Sign up to set email alerts
|

IgG4-related Disease of the Head and Neck: CT and MR Imaging Manifestations

Abstract: Immunoglobulin G4 (IgG4)-related disease is a recently established systemic disease that commonly involves the head and neck, including the salivary glands, lacrimal glands, orbits, thyroid gland, lymph nodes, sinonasal cavities, pituitary gland, and larynx. Although the definitive diagnosis of IgG4-related disease requires histopathologic analysis, elevated serum IgG4 levels are helpful in making the diagnosis. Because of the proposed clinical diagnostic criteria for this disease, cross-sectional imaging moda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
119
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(129 citation statements)
references
References 54 publications
5
119
0
5
Order By: Relevance
“…Inflammatory pseudotumor is a very diverse group of conditions, characterized by acute and chronic inflammatory cells with a variable fibrous response (26,27). On imaging, the disease may manifest as a mass or infiltrating soft tissue lesion involving the orbit, sinonasal cavity, or skull base, with or without bony destruction (23,(26)(27)(28). CT and MRI show various density and signal intensity with frequent hypointensity on T2-weighted images due to the relative lack of mobile protons within fibrotic lesions (27).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory pseudotumor is a very diverse group of conditions, characterized by acute and chronic inflammatory cells with a variable fibrous response (26,27). On imaging, the disease may manifest as a mass or infiltrating soft tissue lesion involving the orbit, sinonasal cavity, or skull base, with or without bony destruction (23,(26)(27)(28). CT and MRI show various density and signal intensity with frequent hypointensity on T2-weighted images due to the relative lack of mobile protons within fibrotic lesions (27).…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of IgG4-RD requires a multidisciplinary approach including various clinical, radiological, and pathological examinations. Radiological findings of major manifestations in various organs, including pancreas, lung, kidney, and aorta/artery, have been published, and radiological examinations and determination of serum IgG4 concentrations are the key steps to achieving the correct diagnosis of IgG4-RD [2,7,[13][14][15][16][17][18]. Although IgG4-RD mainly involves glandular tissues or the vascular system, several case reports have shown that IgG4-RD also involves the gastrointestinal tract with ulcer, polypoid lesions, submucosal mass, and wall thickening.…”
Section: Introductionmentioning
confidence: 99%
“…In the head and neck region, Mikulicz's disease (affecting the salivary and lacrimal glands), Küttner's tumor (affecting mainly the submandibular glands), Riedel's thyroiditis, Hashimoto's thyroiditis, idiopathic orbital inflammatory syndrome, and pituitary hypophysitis may all be attributable to IgG4-RD (Fujita et al 2012;Stone et al 2012). When such conditions are apparent, it is important to investigate the entire body (not just the head and neck).…”
Section: Discussionmentioning
confidence: 99%
“…When such conditions are apparent, it is important to investigate the entire body (not just the head and neck). The salivary glands are the organs most frequently involved in IgG4-RD of the head and neck (Fujita et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation